IJTIHAD DALAM BENTANG SEJARAH PRAKODIFIKASI USHUL FIQH - Jabar, Wahyu Abdul (JURNAL NIZHAM, 2014)
This paper is aimed to know the real description about ijtihad done before the codification of usul fiqh. Theoretically, law product should be establised from theories of usul fiqh, but the realityÂ there are many law products appear before usul fiqh is exists.The laws of islam which is established from ijtihad is different from what we know recently, especially in applying the study of ushul fiqh, it is happened because it is established in the 2nd century of hijriyah. it means that more 200 years, moslems society established the law product without any books about ushul fiqh. where as, it is a must that ijtihad is established after the study of ushul fiqh is exist.From this study, it is know that the product of law is established from Ijtihad which is done before codification of Islamic law in applying the theories of istinbath written in study of ushul fiqh, although this theory has not been written systematically. Ijtihad which is done by sahabat, tabiin and tabi tabiin based on theories of istinbath which is kept well in their chest. They donât learn about the study of usul fiqh from reading a book but directly from their teacher. Something they got from the teacher will be memorized and then they apply it when they face a new cases.Â Keywords: Before Codification, History, Ijtihad, Ushul Fiqh.